PENGARUH PERSEPSI BIDAN PRAKTEK SWASTA TENTANG PROGRAM PROGRAM JAMPERSAL TERHADAP KEMAUAN BIDAN MENJADI PROVIDER PROGRAM JAMPERSAL DI KOTA BINJAI TAHUN 2012 - hessy mayona; Siti Khadijah; Rusmalawaty nasution (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
Abstract Jampersal is an effort that launched by Ministry of Health in order to accelerate the decrease on maternal mortality rate in Indonesia. Binjai District Health Office data shows that the willingness of midwives in private practice in Binjai to be a provider of Jampersal still very low. The type of research was survey with explanatory research that aimed to explain the perception of midwives in private practice on Jampersal (perception of packages, perception of procedures and perception of tariff) against the will of midwives to become the provider of Jampersal in Binjai in 2012. Population were all practicing midwives registered in Binjai District Health Office, as many as 111 people and the establishment of the study sample with simple random sampling. Analysis of the test data used is multiple linear regression with 95% confidence level. The results of the research through multiple logistic regression analysis showed that the variables that influence on the willingness of midwives to be a provider of Jampersal were perception of packets (p < 0.001), the perception of the procedure (p < 0.001) and the perception of tariff (p < 0.001). Tested of three variables, no variable has no effect. Based on the results of the study, it is suggested to the Binjai District Health Officer to improve Jampersal socialization to private practice midwives to enhance their knowledge of the Jampersal so that midwives are not just looking at the Jampersal from previous programs. So that the awareness and willingness of the midwives to be a provider of Jampersal increases.